2016
DOI: 10.1016/s1470-2045(16)30321-7
|View full text |Cite
|
Sign up to set email alerts
|

EANO guidelines for the diagnosis and treatment of meningiomas

Abstract: Although meningiomas are the most common intracranial tumours, the level of evidence to provide recommendations for the diagnosis and treatment of meningiomas is low compared with other tumours such as high-grade gliomas. The meningioma task force of the European Association of NeuroOncology (EANO) assessed the scientific literature and composed a framework of the best possible evidence-based recommendations for health professionals. The provisional diagnosis of meningioma is mainly made by MRI. Definitive dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
599
0
25

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 693 publications
(676 citation statements)
references
References 100 publications
10
599
0
25
Order By: Relevance
“…As a result, deciding on radiotherapy based on the current grading is heavily debated 5 . Thus, we correlated meningioma MCs with progression-free survival (PFS) to evaluate their potential for predicting outcome compared to WHO grading ( Fig.…”
Section: Predict Clinical Course With Higher Accuracy Than Who Gramentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, deciding on radiotherapy based on the current grading is heavily debated 5 . Thus, we correlated meningioma MCs with progression-free survival (PFS) to evaluate their potential for predicting outcome compared to WHO grading ( Fig.…”
Section: Predict Clinical Course With Higher Accuracy Than Who Gramentioning
confidence: 99%
“…subtypes and three grades of malignancy 4 , but some of the diagnostic criteria are vaguely defined and subject to a high inter-observer bias, indicating thea need for more reliable biomarkers 5,7 .…”
Section: Introductionmentioning
confidence: 99%
“…More aggressive anaplastic WHO grade III tumors are likely have mutations in NF2 (10), and meningiomas with mutations in NF2 are found to have significantly lower recurrence-free survival rates (3). Sizes of tumors with NF2 mutations were found to be significantly larger than tumors that do not have mutations in NF2.…”
mentioning
confidence: 95%
“…Initial studies have found that NF2 is one of the most commonly found mutated genes in meningiomas (10). More aggressive anaplastic WHO grade III tumors are likely have mutations in NF2 (10), and meningiomas with mutations in NF2 are found to have significantly lower recurrence-free survival rates (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation